Effects of Rice Trade Policies on Household Welfare in Nigeria (2014)
Inconsistent trade policies have characterised Nigeria’s rice importation, leading to planning and decision-making challenges for producers and consumers, and with fluctuating consequences on welfare status. However, studies on Rice Trade Policy (RTP) have been carried out within the partial equilibrium framework which do not reveal the welfare effects on all sectors and households in the economy. For effective RTP, an understanding of the economy-wide welfare effects is necessary which is possible within a general equilibrium framework. The economy-wide welfare effects of RTPs on households in Nigeria were therefore investigated. Value of domestic production, inputs and intermediate products were obtained from Nigerian Institute for Social and Economic Research’s Input-Output (I-O) table. From the I-O, the economy was grouped into rice, Other Agriculture (OA), Oil and Mining (OM) and Manufacturing and Services (MS) sectors. Household incomes were collected from National Bureau of Statistics’ Nigerian Living Standards Survey (NLSS). From NLSS, households were classified into Rural North Household (RNH), Rural South Household (RSH), Urban North Household (UNH) and Urban South Household (USH). Value of imports and import charges, as measures of Import Tax (IT), were gathered from the Central Bank of Nigeria’s trade summary. All data were for year 2004. Two trade protection policy instruments: Import Ban (IB) and Eighty Percent Tariff Increase (EPTI); and two trade liberalisation policy instruments: Five Percent Tariff Reduction (FPTR) and Tariff Elimination (TE) were identified for simulation. Data were analysed using computable general equilibrium model and Hicksian measures of equivalent variation. Total output valued at ₦11,065 billion comprised MS (42.9%), OM (28.9%), OA (27.5%) and rice (0.7%). Household Income (HI) totaled ₦8,260 billion comprising USH (43.1%), UNH (32.8%), RSH (13.5%) and RNH (10.6%). The IT contributed 77.5% of government revenue. Rice output increased most by 3.1% under TE followed by 1.1% under FPTR. Least increase in rice output of 0.1% occurred under EPTI. Output decreased most in OA (21.7%), OM (0.01%) and MS (0.1%) under TE. However, output increased by 0.5% in OA and decreased least in OM and MS with 0.1% and 0.6% respectively under FPTR. Rural north household had the highest increase in HI of 0.3% under IB but recorded the highest decrease of 17.9% under TE. Least decrease in HI was recorded for RNH (0.1%), RSH (0.01%) and USH (0.2%) under FPTR whereas, UNH income increased by 0.1%. Import ban improved RNH welfare most by ₦2.3 billion while TE decreased it most by ₦115.0 billion. Social welfare loss occurred under all RTPs but was lowest (₦8.0 billion) under FPTR. Highest loss in welfare of ₦694.1 billion occurred under TE. Rural households benefitted under protectionist rice trade policies but the social welfare effect on the economy was negative. However, mild rice trade liberalisation of 5% tariff reduction would minimise Nigeria’s welfare loss from rice trade policies